Majalat al-Tajdid fi Fiqh al-‘Ibadat: Bahts Fiqhiy Muqarin - Fatheya Ismail Muhammad Musy'il (Universitas Darussalam Gontor, 2009)
The renewal in worship has specific characteristics, guidelines and areas. The worship does not accept a development, does not change with time and are not the subject of ijtihad, analogy (qiyas) and consensus of the ummah (ijma’). Islam has specified and made the unchangeable pillars and foundation to form it. Also, Islam has established a certain time, quantity and condition which do not accept changing or interpretation as it contain a commitment of fully worship. In the areas of tajdid in Islamic jurisprudence, there are rules derived from the text (nas) zanny al-tsubut (semi definitive in its affirmation and linkages) or zany al-dilalah (ambiguous/equivocal in the way they relay their meanings) or zanny in one of both (tsubut al-dilalah), here (in these rules) ijtihad can be done. Moreover, as the circumstance and the needs are developed and various, ijtihad is also done in the area in which the text (nas) and consensus are absent. Finally, this ijtihad leads to different opinions among muslim scholars, thus, the comparison area in worship requires three different guidelines i.e. Islamic guidelines, rational knowledgeable guidelines and moral guidelines.